Keberhasilan Kelompok Tani Sekar Mulyo dalam Memengaruhi Kebijakan Pemerintah Kota Batu Tahun 2009-2016 - Regaty, Hisab Akbar (UI Scholars Hub, 2017)
This article will outline the factors that can drive the success of a civil society orga¬nization at the village level in influencing decisions by local governments, with case study of the Sekar Mulyo farmer group in Batu City. The question raised is why the Sekar Mulyo farmer group influences the local agriculture and infrastructure policy more successfully in Batu City in 2009-2016. This article uses qualitative approach by using primary and secondary data. The research found that there are determinants of success are collaborative strategies of civil society organizations, social capital, and clientelistic relation.